Yesus yang Adil - Bakhoh Jatmiko (Sekolah Tinggi Theologia Nazarene Indonesia, 2017)
Textual studies from the Gospel and its historical background reveal that Jesus both, preached forgiveness of sins and provided solutions for the actual needs of people He met. Jesus’ ministries weren’t only for for people’s spiritual needs, but also to break the injustice cycle around Him. The work of Jesus in his ministry is a strong reference to His mission that He came not only to bring people to heaven but also to present heaven to the earth.